2012
DOI: 10.1016/j.bbalip.2011.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Maternal–fetal transfer and metabolism of vitamin A and its precursor β-carotene in the developing tissues

Abstract: The requirement of the developing mammalian embryo for retinoic acid is well established. Retinoic acid, the active form of vitamin A, can be generated from retinol and retinyl ester obtained from food of animal origin, and from carotenoids, mainly β-carotene, from vegetables and fruits. The mammalian embryo relies on retinol, retinyl ester and β-carotene circulating in the maternal bloodstream for its supply of vitamin A. The maternal-fetal transfer of retinoids and carotenoids, as well as the metabolism of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
73
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(75 citation statements)
references
References 148 publications
(202 reference statements)
0
73
0
2
Order By: Relevance
“…That results in a high placental retinol level, which, through negative feedback, can decrease trophoblastic RARα and then RBP expression resulting in decreased pulmonary RBP and retinol level (19). In the circulation, retinol primarily exists in retinol-RBP formation, although at lower concentrations other forms of retinol circulate in the bloodstream such as RE incorporated in lipoprotein particles and RA (6). It has been demonstrated that nitrofen does not disturb the alternative, RBP-independent RE maternal-fetal retinol transport.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That results in a high placental retinol level, which, through negative feedback, can decrease trophoblastic RARα and then RBP expression resulting in decreased pulmonary RBP and retinol level (19). In the circulation, retinol primarily exists in retinol-RBP formation, although at lower concentrations other forms of retinol circulate in the bloodstream such as RE incorporated in lipoprotein particles and RA (6). It has been demonstrated that nitrofen does not disturb the alternative, RBP-independent RE maternal-fetal retinol transport.…”
Section: Discussionmentioning
confidence: 99%
“…The placenta has a major role in retinol homeostasis in fetal life (5). As the fetus cannot synthesize retinol, it relies on circulating maternal retinol, which reaches the fetus by crossing the maternal-fetal barrier in the placenta (6). Although retinol-binding protein (RBP) is essential for retinol transport within the circulation (7), maternal RBP does not cross the placenta (8).…”
mentioning
confidence: 99%
“…In this context, it is important to note that RE from chylomicrons, the major transport mode of dietary vitamin A, can be transferred from the maternal circulation to the embryo (24). Additionally, existing evidence indicates that the maternal vitamin A status can imprint the size of secondary lymphoid organs and the efficiency of immune responses in the offspring (25).…”
Section: Discussionmentioning
confidence: 99%
“…9 In addition, LBW and very LBW prevalence is influenced by risk of disease and lack of prenatal care in some developing countries. 30 Healthy newborn infants from VA-sufficient mothers are already born with limited VA stores due to tight regulation of placental transfer, 4 thus it is not surprising that LBW infants born to mothers who are VA-deficient are compromised. Even in breastfed infants, preterm infants were found to have significantly lower plasma retinol concentrations than term infants at four weeks of age.…”
Section: Discussionmentioning
confidence: 99%
“…3 LBW infants are often underdeveloped physiologically and have minimal VA stores, because of highly regulated trans-placental transport. 4 Preterm infants need VA for proper lung and retina development. 5 Extremely LBW infants (defined as birth weight <1 kg) often have low plasma and tissue concentrations of VA. 6,7 Supplementation trials in LBW infants have yielded contraindicated results.…”
Section: Introductionmentioning
confidence: 99%